Optimizing Three Power Plants”™ Output Power Using Firefly Method - Safarudin, Yanuar Mahfudz; Mariani, Dina (Politeknik Negeri Semarang, 2023)
Continuing the previous article that use merit order, the simplest method in economic dispatch, this article pursue to optimize the output of three power plants using more advanced algorithm, the firefly. The plants used are similar to the previous paper which are three generators used to supply a load of 975 MW. Simulation is used by taking into account losses. The results show that in spite of having higher losses, firefly algorithm managed to calculate a better result than merit orders did by 0,15%.